2016
DOI: 10.1016/j.celrep.2015.12.040
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Delta-like 1 Membrane Dynamics Elucidates the Role of Contact Geometry on Notch Signaling

Abstract: Notch signaling is ubiquitously used to coordinate differentiation between adjacent cells across metazoans. Whereas Notch pathway components have been studied extensively, the effect of membrane distribution and dynamics of Notch receptors and ligands remains poorly understood. It is also unclear how cellular morphology affects these distributions and, ultimately, the signaling between cells. Here, we combine live-cell imaging and mathematical modeling to address these questions. We use a FRAP-TIRF assay to me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 32 publications
4
59
0
Order By: Relevance
“…To experimentally test this prediction, Shaya et al directly measured the dependence of Notch signaling on contact area using a bowtie shaped micro-patterned device with a single sender cell expressing Dll1 ligands and a single receiver cell expressing N1 receptors. Consistent with previous studies (Khait et al, 2016) it was found that Notch signaling was proportional to the contact width, for contact widths ranging from 1–40μm.…”
Section: ) Structural Biology Illuminates Receptor-ligand Interactiosupporting
confidence: 91%
See 1 more Smart Citation
“…To experimentally test this prediction, Shaya et al directly measured the dependence of Notch signaling on contact area using a bowtie shaped micro-patterned device with a single sender cell expressing Dll1 ligands and a single receiver cell expressing N1 receptors. Consistent with previous studies (Khait et al, 2016) it was found that Notch signaling was proportional to the contact width, for contact widths ranging from 1–40μm.…”
Section: ) Structural Biology Illuminates Receptor-ligand Interactiosupporting
confidence: 91%
“…The question of how different contact geometries affect Notch signaling and Notch mediated patterning was recently treated both theoretically and experimentally in two studies by Khait et al and Shaya et al (Khait et al, 2016). In the first study, Khait et al analyzed the interplay between membrane dynamics and contact geometry.…”
Section: ) Structural Biology Illuminates Receptor-ligand Interactiomentioning
confidence: 99%
“…Contact area can be an effective tuning parameter of a biological system (Khait et al, 2016), as it can integrate mechanical constraints into signalling, as has been shown for cell density and proliferative control by the Hippo pathway (Schlegelmilch et al, 2011;Kim et al, 2011;Silvis et al, 2011). In a system such as the posterior midgut, where some differentiated cells are much larger than their progenitors (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The Notch ligand Dalalike 1 (DLL1) gene encodes one of the ligands in the Notch signaling pathway, which is highly conserved to regulate cell fate determination, proliferation, stem cell self-renewal and apoptosis [20]. Phosphatidylinositide 3 kinases (PI3K)/AKT signalling contribute to a variety of processes that are critical in mediating many aspects of cellular function, including nutrient uptake, anabolic reactions, cell growth, migration and survival [21].…”
Section: Introductionmentioning
confidence: 99%